2(2x+7)+3(3x-5)=3(4x+5)-1
Soluções para a tarefa
Respondido por
4
2(2x+7)+3(3x-5)=3(4x+5)-14x+14+9x-15=12x+15-1
4x+9x-12x= 15-1-14+15
x=15
4x+9x-12x= 15-1-14+15
x=15
Respondido por
8
Olá Daniela!
![2 ( 2x + 7 ) + 3 ( 3x - 5 ) = 3 ( 4x + 5 ) - 1 \\ 4x + 14 + 9x - 15 = 12x + 15 - 1 \\ 4x + 9x - 12x = 15 - 1 - 14 + 15 \\ x = 15 2 ( 2x + 7 ) + 3 ( 3x - 5 ) = 3 ( 4x + 5 ) - 1 \\ 4x + 14 + 9x - 15 = 12x + 15 - 1 \\ 4x + 9x - 12x = 15 - 1 - 14 + 15 \\ x = 15](https://tex.z-dn.net/?f=2+%28+2x+%2B+7+%29+%2B+3+%28+3x+-+5+%29+%3D+3+%28+4x+%2B+5+%29+-+1+%5C%5C+4x+%2B+14+%2B+9x+-+15+%3D+12x+%2B+15+-+1+%5C%5C+4x+%2B+9x+-+12x+%3D+15+-+1+-+14+%2B+15+%5C%5C+x+%3D+15)
Tenha bons estudos!
Tenha bons estudos!
danielateodora2:
me ajude a fazer essa x-3(4-x)=7x-(1-x)
Perguntas interessantes
Inglês,
1 ano atrás
História,
1 ano atrás
Biologia,
1 ano atrás
Português,
1 ano atrás
Matemática,
1 ano atrás
Física,
1 ano atrás
Matemática,
1 ano atrás
Biologia,
1 ano atrás